The sensory stimulation programme and neurological Status in stroke: A comprehensive review - Shiroor, Geeta; Bhattacharjee, Tapti (Innovational: Journal of Nursing and Healthcare, 2024)
Human brain has a large capacity for automatic simultaneous processing and integration of sensory information. A sensory system consists of sensory neurons (including the sensory receptor cells), neural pathways, and parts of the brain involved in sensory perception. The combined information from different sensory organs facilitates our ability to detect, discriminate, and recognize sensory stimuli. Many research studies have shown that sensory stimulation program is effective in traumatic brain injury, amnesia, unconsciousness, stroke etc. Depending upon the condition and diagnosis of the patients, the program protocol needs to be decided. The present review focus on the effectiveness of sensory stimulation programme (SSP) on neurological status of patients with stroke. The SSP covered stimulation of all five sensory modalities including tactile, gustatory, olfactory, auditory, and visual senses. Thus it may conclude that the SSP may be helpful to stimulation of all sensory modalities in human being.